Vortex states in Bose-Einstein condensates of a trapped gas - Kobchai Tayanasanti (Chulalongkorn University, 2002)
We study the static and dynamic properties of the trapped Bose gas at the ground state by using the many-body path integral techniques. We obtain the ground state energy of the system and it is in agreement with the results obtained by other methods. The excitation of the condensate by changing the trap strength is investigated. We calculate the density of the system and find that it oscillates with time. The frequency of oscillation we derived coincides with the lowest-lying excitation found in the experiment. Finally, we study the excitation of the condensate with vortex and find the fluctuation in density together with precession of the vortex around the center of the condensate.